On the Bleaching Degree of Multi-Grain Coarse Quartz OSL Signal of Near-Surface Aeolian Sediments Around the Tengger Desert: Empirical Investigation and Numerical Validation - Mo, Hongwei; Peng, Jun; Li, Zhenguo; Song, Yan; Feng, Teng (Frontiers in Earth Science, 2022)
In this study, the degree of bleaching of multi-grain coarse quartz optically stimulated luminescence (OSL) signal of near-surface aeolian samples collected around the Tengger Desert is assessed. The single-aliquot regenerative dose (SAR) protocol and the standardized growth curve (SGC) method are applied to measure the equivalent dose (De) of these samples. The bleaching degree of the samples is assessed by investigating (1) the relationship between Ln/Tn and SAR De and (2) the SGC De distribution. Various degrees of heterogeneously-bleached multi-grain aliquot dose distributions synthetized with a numerical simulation method is further used to validate the bleaching performance of the samples. It demonstrates that the investigated samples are characterized by tight De distributions and the maximum De estimate is smaller than 1.1 Gy. The numerical simulation method which uses as input a large proportion of fully-bleached grains and a small baseline dose is able to reproduce multi-grain De distributions similar to the measured ones. We conclude that OSL signals of multi-grain coarse quartz extracted from most of the investigated aeolian samples are fully bleached before deposition.